An unusual case of unicystic intramural ameloblastoma and review of the literature - Massimiliano Ricci; Francesco Mangano; Paolo Tonelli; Antonio Barone; Cesare Galletti; Ugo Covani (Wolters Kluwer Medknow Publications, 2012)
Ameloblastoma is the most common tumor of odontogenic origin. There are various types of this tumor and confusion still exists among the clinicians about the correct classification. Multicystic ameloblastoma is the most frequent subtype while unicystic ameloblastoma can be considered as a variant of the solid or multycistic. This subtype is considered as a less aggressive tumor with a variable recurrence rate. However, its frequency is often underestimated. The aim of this article is reviewing the recent literature about unicystic ameloblastoma using our unusual clinical case as a starting point to illustrate this discussion. A 30-year-old man who had been complaining of slight pain in the premolar and molar area of the left side of mandible had a check up at our department. X-rays revealed a unilocular radiotrasparency with radiopaque margins. The first histological diagnosis was an odontogenic cyst. Successive histological evaluations revealed that ameloblastic epithelial islands were present in lassus connective tissue. We think that our case report provides new insights into the approach to the ameloblastoma diagnosis. We agree with authors who have pointed out that a single small biopsy may often be inadequate for the correct diagnosis of amelobastoma. Moreover, in the light of our experience, it should be kept in mind that ameloblastomas may have sometimes unusual presentations and this fact should induce surgeons and pathologists to consider carefully each lesion.